Property measurements on spray formed Si-Al alloys - 魏衍广 熊柏青 张永安 刘红伟 王锋 朱宝宏 (Transactions of Nonferrous Metals Society of China, 2007)
A novel Si-Al alloy was prepared by spray forming process for electronic packaging. Property measurements on spray-formed Si-Al alloys after hot pressing were carried out. The results indicate that the alloys （Si-（30%-40%）Al） have advantageous physical and mechanical characteristics, including low coefficient of thermal expansion （6.9× 10^-6 - 8.7 ×10^-6/K）, high thermal conductivity （118-127 W/（m·K））, low density （2.421×10^3 - 2.465×10^3 kg/m^3）, high ultimate flexural strength （180-220 MPa） and Brinell hardness （162-261）. The alloys are easy to machine to tight tolerances using standard machine tools and they can be electroplated with gold finishes and soldered with Sn-Pb alloy without any difficulty.